Combined Symphyseal and Condylar Fractures: Considerations for Treatment in Growing Pediatric Patients. Issue 1 (1st June 2021) - Yesantharao, Pooja S.; Lopez, Joseph; Reategui, Alvaro; Jenny, Hillary; Najjar, Omar; Yu, Jason W.; Yang, Robin; Manson, Paul N.; Dorafshar, Amir; Redett, Richard J.
Abstract : Background: Combined symphyseal-condylar mandible fractures are relatively common but difficult to manage in children. This study investigated the cause and management of symphyseal-condylar fractures in pediatric patients. Methods: This study presents a retrospective review and expert opinion of pediatric symphyseal-condylar mandibular fracture management at the authors' institution between 1990 and 2019. National data from the Healthcare Cost and Utilization Project Kids' Inpatient Database (2000 to 2016) were used to determine whether institutional data had national applicability. Results: Twenty-one patients at the authors' institution met inclusion criteria. Of these patients, 26.7 percent of deciduous dentition patients underwent open reduction and internal fixation, 40 percent underwent closed treatment (maxillomandibular fixation), and 33.3 percent received a soft diet. All mixed dentition patients underwent open reduction and internal fixation or closed treatment; all permanent dentition patients underwent open reduction and internal fixation. The national database ( n = 1708) demonstrated similar treatment patterns: most permanent dentition patients (88.7 percent) underwent open reduction and internal fixation, most mixed dentition patients (79.2 percent) underwent closed treatment, and among deciduous dentition patients, 53.5 percent patients received a soft diet; 38 percent received closed treatment. In this study, the overall posttreatment complication rate was 62.5 percent among open reduction and internal fixation patients, 14.3 percent among closed treatment patients, and 16.7 percent among patients treated with a soft diet. Conclusions: Symphyseal-condylar mandibular fractures were associated with substantial morbidity in children. The authors created a treatment algorithm to maximize outcomes in children who suffer from this challenging fracture pattern. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.